Identification of Feeder Station Interior Wayfinding Elements Based on Universal Design Through Systematic Literature Review - Rahmawityana, Dyah Ellne; Adhitama, Gregorius Prasetyo (Sinektika: Jurnal Arsitektur, 2026)
Feeder Train Services serve as a strategic solution in strengthening connectivity between KCJB main stations and urban areas such as Bandung and Cimahi. This study aims to analyze the evaluation methods or conditions of universal design-based interior wayfinding elements applied at Jakarta-Bandung Fast Train (KCJB) feeder stations. This study uses a Systematic Literature Review (SLR) approach with a descriptive qualitative design to identify universal design-based interior wayfinding elements at feeder stations by analyzing academic articles and grey literature from the Scopus and Google Scholar databases between 2021 and 2025. This study describes the regulations and standardization of interior wayfinding components at train stations by reviewing visual, technical, and spatial elements. The results of the literature review show that the evaluation of wayfinding implementation can be done through direct observation and questionnaires for users. This wayfinding evaluation needs to be applied, especially on feeder trains, which will effectively improve user movement efficiency, safety, and overall travel experience, as well as strengthen the integration of public transportation services in metropolitan areas. Furthermore, the literature review also emphasizes that the integration of conceptual evaluation and technical standards in wayfinding is crucial to improve user orientation, accessibility, and travel efficiency, thereby supporting safety and multimodal connectivity at KCJB feeder stations.